Glass Ceiling Effect in What Men Want Movie (2019) - Dian Ari Safitri; Ririn Kurnia Trisnawati; Mia Fitria Agustina (Universitas PGRI Madiun, 2022)
The glass ceiling effect is a phenomenon that often happens in society but is still rarely addressed. It is because this phenomenon is oftentimes hard to notice since we are already used to it. However, this kind of issue is apparent in What Men Want (2019) movie. This current study aims to analyze the glass ceiling effect faced by the main character in the movie, Ali Davis. The method used to help analyze the data is a qualitative method by taking dialogues from the movie as the main data of this research. The result shows the aspects that indicate the glass ceiling effect in the movie are the employee promotion system, discrimination from male coworkers, and discrimination from a prospective client. Eventually, this study reveals that the glass ceiling effect still occurs in the modern era. Therefore, this current study suggests that companies have to be mindful when they set policies and a good understanding of gender equality among people in the workplace is also needed to minimize the similar cases.